Promoting Teachers' Ideological Becoming: Using Dramatic Inquiry in Teacher Education. (November 2016) - Edmiston, Brian
Freedman and Ball propose a language, literacy, and learning research agenda meant for practitioners as well as researchers, which they locate in Bakhtin's notion of development, or "ideological becoming." Language and literacy educators change how they teach when they come to see themselves differently in relation to the students in their classrooms. This article provides a theory and description of practice that suggests potential productive uses of a dramatic inquiry-based dialogic pedagogy in college classrooms intended to promote teachers' ideological becoming. After first contextualizing Freedman and Ball's research agenda in terms of current teacher education practices and challenges, including an oppressive status quo in our increasingly culturally and ethnically diverse schools and colleges, and then providing a theoretical framework, a teacher educator–researcher describes his use of dramatic inquiry pedagogy using carefully chosen picture books in an MA class for domestic and international students, which provided participants with opportunities to dialogue with different schooling practices and thus develop their own ideologies. Analysis of narrative responses from three teachers indicates their ideological development in relation to promoting inclusion and antioppressive practices as an integral part of their language and literacy teaching.